THE RELATION BETWEEN CLINICAL SIGNS, PARAMETERS OF HEART RATE VARIABILITY AND FUNCTION OF EXTERNAL BREATHING IN THE PATIENT WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE BEFORE AND AFTER THERAPY - Bondarenko, I.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The relation between clinical signs, parameters of the heart rate variability (HRV) and function of an external breathing (FEB) was studied in the patient with chronic obstructive pulmonary disease (COPD) before and in 1 month of therapy. 74 patients with II-IV stages of COPD were investigated. The health history, the data oh physical examination, laboratory and instrumental data were examined. The estimated parameters of FEB were next: respiration rate (RR), forced exhalation volume per 1 second (FEV1), relation of FEV1 to forced vital capacity. Among the HRV parameters, we estimated heart rate (HR), total power (ТР) and its components in domains of very low frequencies (VLF), low frequencies (LF), high frequencies (HF) and LF/HF relation. The results shows clinical symptoms of COPD improved with inauthentic increase of FEB parameters and ТР HRV increase in the presence of LF/HF decrease on therapy stage.